KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Buhari Muslim (UNISAN JURNAL, 2024)
This exploration plans to decide the connection between the character skill of Islamic Strict Schooling (PAI) educators and understudy learning inspiration at SMPN 2 Medan. This examination utilizes a quantitative methodology with a correlational plan. The examination test comprised of 150 understudies in grades 4, 5, and 6 who were picked arbitrarily. Information was gathered through a poll that deliberate PAI educators’ character skills utilizing a Likert scale and understudy learning inspiration. Information examination was completed utilizing spellbinding measurable methods and Pearson connection. The exploration results show that PAI instructors’ character capabilities, for example, compassion, honesty, relational abilities and relational abilities emphatically affect understudy acquiring inspiration. PAI instructors who have higher character skill will generally have the option to establish a more favorable learning climate, grasp understudies’ requirements, and offer the important help to expand their learning inspiration. Second, these discoveries show that understudies’ learning inspiration at SMPN 2 Medan is somewhat high, both with regards to inherent and extraneous inspiration. A solid interest in Islamic strict learning and a drive to accomplish great scholastic accomplishments are qualities of understudies at SMPN 2 Medan